A study on the extraction method and the stability of blue pigment from various natural source for food coloring: article - Abdul Rashid, Muhammad Arshad; Maqsood Ul Haque, Siti Noor Suzila (2017)
The demand for natural food colouration keep on increasing annually after the benefits of natural colour which are not only for food colouring but also have abundance of health effect have been revealed. However, there is a major factor that prevent these natural colour from being commercialize which is its stability. Natural colour such as anthocyanin have weakness in heat, light, storage time and many other external factors that usually done in industry. Therefore, this experiment was done to determine the better extraction method and to test the extracted pigment stability in food product. The natural colour sources come from Clitoria ternatea and Melastoma malabathricum, fruits which gives blue colour. The solvent used for the extraction are deionized water and ethanol. The stability test will be conducted on the encapsulated liquid, the encapsulated powder and on the muffins, that contain these encapsulated dye pigment. For the extraction procedure, the pigment that extract using solvent show higher absorbance compared to others. For the stability on encapsulated solution and on powder, higher temperature affects more on colour degradation compared to lower temperature while for storage time, longer time also would affect on colour degradation on powder also muffin. For C. ternatea, the solution extract with ethanol 20% have higher reading on spectrophotometer which is 2.807 compared when extract with deionize water which is 1.69 at 600nm. While for M. malabathricum, the solution extract with ethanol 20% also have higher reading on spectrophotometer which is 2.05 compared when extract with deionize water which is 1.706 at 800nm. In powder test, C. ternatea with water extract shows highest reading in chromameter for lightness test. For coordinate a*, M. malabathricum extract with ethanol 20% shows highest reading while coordinate b* M. malabathricum with deionize water extract have highest reading. The time for testing the sample are at days (0,7,14,21 and 28). The different temperature used are room temperature (25°C) and refrigerator (4°C) while the presence of light is tested by wrapping and unwrapping the sample using aluminum foil. Therefore, it is observed that temperature, storage time and light gives impact on the stability of anthocyanin blue colour.